3p-2q=-9

Simple and best practice solution for 3p-2q=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p-2q=-9 equation:


Simplifying
3p + -2q = -9

Solving
3p + -2q = -9

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2q' to each side of the equation.
3p + -2q + 2q = -9 + 2q

Combine like terms: -2q + 2q = 0
3p + 0 = -9 + 2q
3p = -9 + 2q

Divide each side by '3'.
p = -3 + 0.6666666667q

Simplifying
p = -3 + 0.6666666667q

See similar equations:

| 3w^2-4w=84 | | 10x+5y-5=170 | | 7m+11=-88 | | 6n+11=27 | | p+1(p+3)(p+7)= | | 2m+11=-88 | | .625x=20 | | -7+2(x-3)= | | .17x=3 | | 0=0.25x+1 | | log(x^2+4)-log(x+2)=2+log(x-2) | | .7(x)=58 | | .7(x)=41 | | .7(x)=31 | | .7(x)=11.07 | | .7(x)=6.16 | | .7(x)=7.16 | | .7(x)=8.10 | | -3v=195 | | (5n+2)(3n-7)=0 | | (9-x)(2x^2-4)(9x^3+6x-27)(5x-2)=0 | | .7(x)=7.50 | | 3x^3+2x^2+4=28 | | .7(x)=3.90 | | 7(x)=3.90 | | .7(x)=6 | | .7(x)=5 | | .3(x)=5 | | 5.99x+2.05= | | 3x-11=1-x | | 5(y-2)-y=42 | | 1.3(x)=5 |

Equations solver categories